Empowering Women Food Entrepreneurs: Unveiling their Social Commerce Readiness and Digital Challenges (Journal of Entrepreneurship and Business, 2025)
This study investigates the readiness of women-owned small and medium-sized enterprises (SMEs) to engage in social commerce and its implications for business readiness. Utilizing a quantitative research design with purposive sampling, data were collected from 2024 women-owned SME owners through an online survey. The study reveals strong positive correlations between social commerce activities, technological information gaps, financial conditions, and the readiness of women-owned SMEs Specifically, increased engagement in social commerce significantly enhances business preparedness, while gaps in technological information and financial constraints pose substantial challenges. The findings point out the importance of bridging these gaps by providing adequate technological and financial support to empower women entrepreneurs in Kuala Selangor.  Such support is crucial for fostering the growth and success of women-owned SMEs in the region's increasingly digitalized business landscape. Practically, the findings suggest that policymakers and support agencies should prioritize tailored training programs and financial support to empower women-owned SMEs with the tools and knowledge needed for successful engagement in social commerce. This study highlights the need for targeted policies and initiatives within Selangor to address these challenges, ensuring that women-owned SMEs in the region can fully participate in and benefit from the digital economy.
Keywords: Array; Array; Array